1998
DOI: 10.1159/000007119
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Testing (Agar Disk Diffusion and Agar Dilution) of Clinical Isolates of <i>Corynebacterium jeikeium</i>

Abstract: Thirty-three clinical isolates of Corynebacterium jeikeium were examined for susceptibility to 27 antimicrobial drugs with the agar dilution test. Sheep-blood-supplemented Mueller-Hinton agar performed better than Wilkins-Chalgren agar. Disk susceptibility (Bauer-Kirby) tests were carried out in parallel with 24 of the chemotherapeutic agents. All isolates were susceptible to teicoplanin and vancomycin. All isolates resisted fosfomycin, mupirocin, and trimethoprim-sulfamethoxazole. The isolates varied in susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…Another discord with earlier reports was revealed in case of TMP/SMX that was highly active on the majority of the strains studied by us while weak or missing activity of it against C. striatum, C. jeikeium, D. hominis and T. otitidis has been described [18][19][20]. Our results justify the role of TMP/SMX as the drug of choice for prostatitis in Canada [21].…”
Section: Mic (μG/ml)contrasting
confidence: 65%
“…Another discord with earlier reports was revealed in case of TMP/SMX that was highly active on the majority of the strains studied by us while weak or missing activity of it against C. striatum, C. jeikeium, D. hominis and T. otitidis has been described [18][19][20]. Our results justify the role of TMP/SMX as the drug of choice for prostatitis in Canada [21].…”
Section: Mic (μG/ml)contrasting
confidence: 65%
“…Colonization of such indwelling devices as central venous catheters by C. jeikeium is a common problem among immunocompromised patients and may be associated with consecutive bacteremia and septic infections (7). Accordingly, C. jeikeium has already been considered as an opportunistic pathogen which easily acquires resistance to various antibiotic agents (19). In the present case, the changing antibiotic combinations over more than 2 weeks (from days Ϫ7 to ϩ8 [ Fig.…”
mentioning
confidence: 87%
“…Antimicrobial susceptibility studies revealed that a preponderant proportion of the reported C. jeikeium isolates are substantially multiresistant against clinically relevant antibiotics and that only glycopeptides, such as vancomycin and teicoplanin, remain universally active against this species (4,38,79). This emergence of multiresistant phenotypes largely limits the therapeutic options and has thus tremendous consequences for successful treatment of C. jeikeium infections, especially in immunocompromised patients.…”
mentioning
confidence: 99%